Couples Considering a Blended Family - Kate Fogarty; Millie Ferrer; Sara McCrea; Evelyn Rooks-Weir (EDIS, 2006)
Revised! FCS2148, a 6-page fact sheet by Kate Fogarty, Millie Ferrer, and Sara McCrea, provides guidance, questions to help assess family views, and tips for couples considering a blended family. This version is expanded from four to six pages, and adds color illustrations, additional material on teenage children in blended families, resources and references. Published by the UF Department of Family Youth and Community Sciences, June 2006.